Evaluation of entrapment potentiality and turbidity removal efficiency of fungi - Jebun, N.; Al-Mamun, Abdullah; Alam, Md Zahangir; Abdul Karim, Mohamed Ismail; Ahmad Raus, Raha (Universiti Teknologi Malaysia, 2015)
Turbidity and suspended solids concentration promotes a number of negative effects on freshwater ecosystems. Conventionally suspended solids and turbidity are removed from raw water by various chemical coagulants but most of them are costly and non-ecofriendly. Whereas, the bioflocculants are environment-friendly and could be used as coagulants. Extracellular polymeric substances (EPS) produced by microorganisms play a definite role to reduce the turbidity of river water which can enhance the aesthetics of river water and other water uses. In this study, pellets /flocs have been observed of five filamentous fungi isolated from Pusu river water. The strains RWF-01, RWF-02, RWF-03, RWF-04 and RWF-05 showed a good entrapment capability and flocculating rate of 97.56%, 99.42%, 99.18%, 59.34% and 85.21% to kaolin suspension and 44.54%, 99.27%, 98.59%, 28.57% & 68.43% to river water respectively at 48h of culture time. The result showed the clay particles of river water and kaolin has entrapped by the microbial growth and, as a result, they reduced the turbidity of river water.